Adult-onset Stills Disease from Dermatological Perspective: A Case with Atypical Cutaneous Manifestation - Vargu, Migena; Vargu, Petrit; Dedej, Sabina; Kurushi, Eriselda; Vargu, Samuele; Fero, Henri; Tan-Wohlers, Jaclyn; aliu, Ermira; Awad, Abdelrahman; Gamal, Mohamed; Mian, Hafsa Safer; Fahad, Farah; et al. (Archives of Clinical and Biomedical Research, 2025)
Still's disease is a rare and complex systemic autoinflammatory disorder. Characterized by high fevers, salmon-colored rash, and joint involvement, this condition can be a challenging diagnosis due to its overlapping symptoms with other illnesses [1,2]. First described by British physician Sir George Still in 1897, the disease manifests in both systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still's disease (AOSD), each carrying its own set of clinical nuances and implications [3,4]. Epidemiological data on AOSD are characterized by a prevalence estimated at 0.73 to 6.77 per 100,000 individuals, a bimodal age distribution with two peaks of onset (the age groups of 16–25 years and 36–46 years), a mean age of approximately 38 years and without sex predilection [5-7]. Recent advancements in medical research have shed light on the pathophysiology of Still's disease, emphasizing the role of genetics and immune system components such as cytokines and infectious agents [7,8]. Otherwise, the exact etiology is still unknown. Diagnosing AOSD is challenging due to the absence of pathognomonic clinical signs or serologic markers. Here we present a patient with atypical cutaneous manifestations associated with adult-onset Still disease.